Innovative Startup Financing Models: Venture Capital and Crowdfunding - Sukachova, Snizhana; Vytrykhovskyi, Yevstakhii; Korneev, Volodymyr; Gaponiuk, Mykola; Borodenko, Tetiana (International Journal of Economics and Financial Issues, 2025)
In Ukraine, the lack of efficient financing mechanisms impedes the growth of startups. Therefore, venture capital and crowdfunding models need to be compared. The main task of the research is to assess the efficiency of using these financing models in Ukraine during 2024. The study uses a mixed regression analysis method, case studies about successful Ukrainian startups, and SWOT analysis to compare these financing mechanisms. The results show that venture capital has a strong positive impact on startup success (β = 0.72, p < 0.01), whereas crowdfunding is positively related (β = 0.54, p < 0.05). However, it is with higher risk. In addition, the results point out that the involvement of investors and the amount of time needed to raise funds are essential factors for financing success. As laid out in the SWOT analysis, the most significant strengths of venture capital are strategic mentorship and scalability, while crowdfunding can help you better validate the market. The hybrid financing framework with venture capital’s structured investment and crowdfunding’s accessibility should be used as a key policy implication to enhance startup growth in Ukraine.